PERANCANGAN SISTEM INFORMASI PEMESANAN SLOT PARKIR BERBASIS ANDROID (studi kasus : Sumarecon Mall Bekasi) - Wicaksono, - (2018)
The availability of parking slot is a must for mall customers with vehicle, difficulty to get a parking slot when the customers traffic is crowded often found. Service which given by the mall needs to be developed for customers sake. Research Method which used in this research is Waterfall also using MySQL to design database and using PHP as well as Android Studio to create an android based parking slot booking application for improving a safe and efficient parking service. Based on the result of Designing Parking Slot Booking Android Based Information System, the conclusion that can be drawn is this system provides service for customers to book a parking slot before they arrive in parking area, so costumers already have a parking slot without a need to look for an empty slot. As for the advice that can be given in the system that have been created, is installation of parking censors in every parking slots for integrating application that has been created with those censors, so update procedures can be done realtime and without need of an admin